Philosophy and literature: in the traces of democracy - Maurel, Jean (Estudios de Filosofía, 2003)
Starting from the question made by Derrida about the suspicious absence of democratic philosophers from Plato to Heidegger, the article thinks over the relationship that democracy and literature have held with philosophy. Assuming the former as the game of diversity of beings, the exchange of words in a no-win combat, which is peculiar of agon and pólemos, it is shown how at its platonic beginning, philosophy institutes its ideal of Meaning Goodness and Truth opposing, precisely democratic agitation. But an the other hand, critical Kantian thinking outstands as an opening moment to the plural relationship of beings Possessing, from its beginning as mythology, the critical strength of this thinking is what allows literature to reach the traces of democracy.